Nitrogen and phosphorus co-doped graphene quantum dots: synthesis from adenosine triphosphate, optical properties, and cellular imaging. Issue 17 (15th April 2015) - Ananthanarayanan, Arundithi; Wang, Yue; Routh, Parimal; Sk, Mahasin Alam; Than, Aung; Lin, Ming; Zhang, Jie; Chen, Jie; Sun, Handong; Chen, Peng
Abstract : N/P co-doped graphene quantum dots are synthesized, characterized, and used for specific molecular imaging and tracking in live cells. Abstract : Graphene quantum dots (GQDs) are emerging zero-dimensional materials promising a wide spectrum of applications, particularly, as superior fluorescent reporters for bio-imaging and optical sensing. Heteroatom doping can endow GQDs with new or improved photoluminescence properties. Here, we demonstrate a simple strategy for the synthesis of nitrogen and phosphorus co-doped GQDs from a single biomolecule precursor (adenosine triphosphate – ATP). Such ATP-GQDs exhibit high fluorescence quantum yield, strong two-photon upconversion, small molecular weight, high photostability, and good biocompatibility. Furthermore, transferrin conjugated ATP-GQDs have been used for imaging and real-time tracking of transferrin receptors in live cells.